Characterization of two infection‐induced transcription factors of Magnaporthe oryzae reveals their roles in regulating early infection and effector expression. (17th April 2022) - Cao, Yiyang; Chen, Jia; Xie, Xuze; Liu, Shenghua; Jiang, Yue; Pei, Mengtian; Wu, Qianfei; Qi, Pengfei; Du, Lili; Peng, Baoyi; Lan, Jianwu; Wu, Fan; et al.
Abstract: The initial stage of rice blast fungus, Magnaporthe oryzae, infection, before 36 h postinoculation, is a critical timespan for deploying pathogen effectors to overcome the host's defences and ultimately cause the disease. However, how this process is regulated at the transcription level remains largely unknown. This study functionally characterized two M .  oryzae Early Infection‐induced Transcription Factor genes ( MOEITF1 and MOEITF2 ) and analysed their roles in this process. Target gene deletion and mutant phenotype analysis showed that the mutants Δ moeitf1 and Δ moeitf2 were only defective for infection growth but not for vegetative growth, asexual/sexual sporulation, conidial germination, and appressoria formation. Gene expression analysis of 30 putative effectors revealed that most effector genes were down‐regulated in mutants, implying a potential regulation by the transcription factors. Artificial overexpression of two severely down‐regulated effectors, T1REP and T2REP, in the mutants partially restored the pathogenicity of Δ moeitf1 and Δ moeitf2, respectively, indicating that these are directly regulated. Yeast one‐hybrid assay and electrophoretic mobility shift assay indicated that Moeitf1 specifically bound the T1REP promoter and Moeitf2 specifically bound the T2REP promoter. Both T1REP and T2REP were predicted to be secreted during infection, and the mutants of T2REP were severely reduced in pathogenicity. Our results indicate crucial roles for the fungal‐specific Moeitf1 and Moeitf2 transcription factors in regulating an essential step in M .  oryzae early establishment after penetrating rice epidermal cells, highlighting these as possible targets for disease control. Abstract :